2012
DOI: 10.3319/tao.2012.01.12.01(t)
|View full text |Cite
|
Sign up to set email alerts
|

Remote Triggering of the Mw 6.9 Hokkaido Earthquake as a Result of the Mw 6.6 Indonesian Earthquake on September 11, 2008

Abstract: Only just recently, the phenomenon of earthquakes being triggered by a distant earthquake has been well established. Yet, most of the triggered earthquakes have been limited to small earthquakes (M < 3). Also, the exact triggering mechanism for earthquakes is still not clear. Here I show how one strong earthquake (M w = 6.6) is capable of triggering another (M w = 6.9) at a remote distance (~4750 km). On September 11, 2008, two strong earthquakes with magnitudes (M w ) of 6.6 and 6.9 hit respectively in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Great earthquakes commonly generate both instantaneous and delayed seismicity at distances of hundreds to thousands of kilometres, where static stress changes are negligible, but these remote aftershocks usually have small magnitudes and often occur in volcanic or geothermal areas with quite different stress and frictional regimes [34][35][36] . A notable exception was a M w 6.9 earthquake in Japan that initiated during the passage of surface waves from a M w 6.6 event in Indonesia, confirming the potential for larger triggered earthquakes in compressive environments 37 . However, whether dynamic triggering also occurs locally (within 1 -2 fault lengths of the triggering event) is still controversial, in part because deconvolving static and transient stress changes within this area is challenging [38][39][40][41] .…”
Section: Triggering Mechanismmentioning
confidence: 90%
“…Great earthquakes commonly generate both instantaneous and delayed seismicity at distances of hundreds to thousands of kilometres, where static stress changes are negligible, but these remote aftershocks usually have small magnitudes and often occur in volcanic or geothermal areas with quite different stress and frictional regimes [34][35][36] . A notable exception was a M w 6.9 earthquake in Japan that initiated during the passage of surface waves from a M w 6.6 event in Indonesia, confirming the potential for larger triggered earthquakes in compressive environments 37 . However, whether dynamic triggering also occurs locally (within 1 -2 fault lengths of the triggering event) is still controversial, in part because deconvolving static and transient stress changes within this area is challenging [38][39][40][41] .…”
Section: Triggering Mechanismmentioning
confidence: 90%
“…Large earthquakes trigger very small earthquakes globally during passage of the seismic waves and during the following several hours to days 1-10 , but so far remote aftershocks of moment magnitude M $ 5.5 have not been identified 11 , with the lone exception of an M 5 6.9 quake remotely triggered by the surface waves from an M 5 6.6 quake 4,800 kilometres away 12 . The 2012 east Indian Ocean earthquake that had a moment magnitude of 8.6 is the largest strikeslip event ever recorded.…”
mentioning
confidence: 99%
“…Pollitz et al (2012) suggested that the East Indian Ocean earthquake triggered large aftershocks worldwide. Lin (2012), argued that the Mw 6.6 Indonesian earthquake triggered the Mw 6.9 Hokkaido Earthquake on September 11, 2008. These observations, and many others, suggest that there is a systematic, and discernable global pattern, where an earthquake in one geographical area, is statistically linked to an earthquake in a remotely located area thousands of kilometers away.…”
Section: Introductionmentioning
confidence: 99%